3D fibre reinforced polymer composites - Tong, Liyong, 1963-; Mouritz, Adrian P.; Bannister, Michael K. (Boston : Elsevier, 2002)
Fibre reinforced polymer (FRP) composites are used in almost every type of advanced engineering structure, with their usage ranging from aircraft, helicopters and spacecraft through to boats, ships and offshore platforms and to automobiles, sports goods, chemical processing equipment and civil infrastructure such as bridges and buildlings. The usage of FRP composites continues to grow at an impessive rate as these materials are used more in their existing markets and become established in relatively new markets such as biomedical devices and civil structures. A key factor driving the increased applications of composites over the recent years is the development of new advanced forms of FRP materials. This includes developments in high performance resin systems and new styles of reinforcement, such as carbon nanotubes and nanoparticles. This book provides an up-to-date account of the fabrication, mechanical properties, delamination resistance, impact tolerance and applications of 3D FRP composites. The book focuses on 3D composites made using the textile technologies of weaving, braiding, knitting and stiching as well as by z-pinning.
Introduction. Manufacture of 3D Fibre Preforms. Preform Consolidation. Micromechanics Models for Mechanical Properties. 3D Woven Composites. Braided Composite Materials. Knitted Composite Materials. Stitched Composites. Z-Pinned Composites.
Includes bibliographical references and index.
Keywords: Fiber-reinforced plastics; Polymeric composites; Electronic books